A systematic review and meta-analysis of quality of life outcomes after radical cystectomy for bladder cancer. (September 2016) - Yang, Linda S.; Shan, Bernard L.; Shan, Leonard L.; Chin, Peter; Murray, Spencer; Ahmadi, Nariman; Saxena, Akshat
Abstract: Background: Radical cystectomy and urinary diversion is the treatment of choice for invasive bladder cancer. Quality of life (QOL) is an important outcome of surgery. This review compares the QOL after continent and incontinent urinary diversion in radical cystectomy for patients with primary invasive bladder cancer. Methods: A systematic review and meta-analysis of clinical studies published after January 2000 was performed according to the PRISMA guidelines. Quality appraisal and data tabulation were performed using pre-determined forms. Data were synthesised by narrative review and random-effects meta-analysis using standardized response means. Heterogeneity and bias was assessed by Tau 2 and I 2 values and Funnel plots. Results: Twenty-nine studies (3754 patients) were included for review. Pooled post-operative FACT and SF-36 scores showed no difference in overall QOL between continent and incontinent diversion ( p = 0 . 31 ). Subgroup analysis demonstrated greater improvement in physical health for incontinent ( p = 0 . 002 ) compared to continent diversions, but no differences in mental health ( p = 0 . 35) and social health ( p = 0 . 81) . Qualitative analysis showed patients with neobladder had superior emotional function and body image compared to cutaneous diversion. QOL may improve to similar or better levels compared to baseline after 1 year, but data remains scarce. Patients report poor urinary and sexual function after surgery compared the general population. Long-term QOL is unclear. Levels of heterogeneity and bias were low. Conclusions: QOL after radical cystectomy is comparable after either continent or incontinent urinary diversion. Post-operative QOL may improve, but urinary and sexual dysfunction remains inferior to the general population. Patient choice is key to selection of reconstruction method.